In-silico identification and characterization of O-methyltransferase gene family in peanut (Arachis hypogaea L.) reveals their putative roles in development and stress tolerance - Cai, Tiecheng; Sharif, Yasir; Zhuang, Yuhui; Yang, Qiang; Chen, Xiangyu; Chen, Kun; Chen, Yuting; Gao, Meijia; Dang, Hao; Pan, Yijing; Raza, Ali; Zhang, Chong; et al. (Frontiers in Plant Science, 2023)
Cultivated peanut (Arachis hypogaea) is a leading protein and oil providing crop and food source in many countries. At the same time, it is affected by a number of biotic and abiotic stresses. O-methyltransferases (OMTs) play important roles in biotic and abiotic stress tolerance through different metabolic processes. However, the OMTs genes have not been comprehensively analyzed in peanut. A comprehensive genome-wide analyses was carried out to identify the OMT genes in peanut genome. Chromosomal organization, gene structure, phylogenetic relations, protein interactions, collinearity, and gene duplication were studied. Different cis-elements on OMT promoters, miRNAs were also predicted, and expression matrices in different organs and stresses were also examined. In peanut genome, 116 OMT (AhOMTs) members were found. Phylogenetically, AhOMTs were clustered into three groups. Tandem and segmental duplication played role in the evolution of AhOMTs and purifying selection pressure drove the duplication process. AhGLPs promoters were enriched in several key cis-elements including 'growth and development', 'phytohormones', 'light induction', and defense-related elements. Micro-RNAs from 12 different families targeted 35 AhOMTs. GO enrichment analysis indicated that AhOMTs are highly enriched in transferase and catalytic activities, cellular metabolic and biosynthesis processes. AhOMTs recorded expression variance in different tissues. AhOMT32-AhOMT35, AhOMT45, AhOMT71, AhOMT106, AhOMT113, AhOMT114, and AhOMT116 were expressed in leaf, stem, flower, root, root nodule, peg, pericarp, testa, cotyledon, and embryo. AhOMT9 and AhOMT46 specifically showed high expression in root nodules. AhOMT35, AhOMT71, AhOMT106, and AhOMT113 were expressed under most of stress conditions. These findings are valuable for future functional studies on the AhGLPs for peanut breeding programs.